Assessing the productivity of PAs and NPs. Issue 11 (November 2022) - Stefos, Theodore; Moran, Eileen A.; Poe, Stacy A.; Hooker, Roderick S.
ABSTRACT: The improvement of healthcare efficiency and productivity is of international interest. Following an expansion phase of physician associate/assistant (PA) and NPs employment, the Department of Veterans Affairs (VA) assessed how and where they were being used. Using data from 134 VA medical centers, annual productivity was examined across 30 medical and surgical specialties spanning primary care, mental health, and surgery. PA productivity differences averaged 82 relative value units per full-time employee per year more than NPs, a difference of 4%. In general, PAs were found in higher productivity ranges than NP counterparts. PAs and NPs have statistically similar productivity levels in primary care and mental health. In specialty medicine and surgery, PAs average higher annual productivity than NPs. This analysis provides some utility for managers regarding workforce composition, given the relative productivity of two types of clinicians.